AN ANALYSIS OF THE NATIONAL CHARACTER BUILDING OFSONGSLYRICS: STAND OUT FIT IN, A MILIONS DREAMS AND BY MY SIDE - Wibowo , Joko; Arifin, Zainul (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2023)
In the era of globalization and modernization, every nation has the opportunity to become an advanced and independent nation, but if the nation does not have strong character and resilience, modernization and globalization will bring threats to the nation. Both "personality" and "character" are interchangeable concepts. Both of these are considered as traits based on a person's social formation. Character is defined as a unique characteristic, quality, style, or personality of a person based on the formation of society in the book Mutmainnah. Many researchers make literary works such as song lyrics, novels, and so on as objects in their research because literary works are considered the easiest objects to analyze. However, only a few of them have researched the development of the nation's character in literary works. In fact, the formation of national character is very important for students in the world of education so that it attracts researchers to conduct this research. The aims of this research are (1) To identify the national characters building that appear in song lyrics of Stand out fit in, A millions dreams and By my side. (2) To describe the contextual meanings of the national character building found in the selected songs‟ lyrics. The researcher chose descriptive qualitative as the research design because the researcher wanted to analyze and report the results and findings using words rather than numbers. In analyzing the data, this study uses content analysis techniques by comparing data, making categorizations, presenting data tabulations, verbally describing, and interpreting findings to make inferences. The results showed that: The researcher found 4 national characters in “Stand out fit in song” that has been analyzed into 3 independents, 1 hardworking, 1 love of peace. In “A million dreams song” the researcher found 5 National character building that has been analyzed into 2 Curious, 1 independent, 1 Communicative, 1 peace loving, 1 Tolerance. Then in “by my side song” the researcher found 2 National character building that has been analyzed into 1 curious, 3 peace loving.